Magnetic field assisted photocatalytic degradation of organic dyes in the presence of Ag - Wang, Jian (Water Science and Technology)
Ag/TiO2 coated composite was prepared via sol-gel method in order to elucidate its application in magnetic field assisted photocatalytic degradation of dyes. Through the degradation of organic dyes, the key influences such as Ag amount, heat-treated temperature and time on the photocatalytic activity of Ag/TiO2, as well as UV irradiation time, rotational speed, dye concentration and magnetic sheet number on the photocatalytic degradation were studied. Results showed that the Ag/TiO2 with 25 wt% Ag content heat-treated at 550 °C for 60 min has the best photocatalytic activity. With the increase of UV light irradiation time, rotational speed and magnetic sheet number, the degradation rate is improved. Different dye degradation proved that the method could universally be used.